2003
DOI: 10.1126/science.1082192
|View full text |Cite
|
Sign up to set email alerts
|

The Division of Endosymbiotic Organelles

Abstract: Mitochondria and chloroplasts are essential eukaryotic organelles of endosymbiotic origin. Dynamic cellular machineries divide these organelles. The mechanisms by which mitochondria and chloroplasts divide were thought to be fundamentally different because chloroplasts use proteins derived from the ancestral prokaryotic cell division machinery, whereas mitochondria have largely evolved a division apparatus that lacks bacterial cell division components. Recent findings indicate, however, that both types of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
231
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(236 citation statements)
references
References 77 publications
3
231
0
2
Order By: Relevance
“…NbGyrA, NbGyrB, and other plant DNA gyrase subunits contain an N-terminal extension that features chloroplast and mitochondria targeting signals (Emanuelsson and von Heijne, 2001). Of the prokaryotic GyrA and GyrB sequences, those of cyanobacterial species are most closely related to NbGyrA and NbGyrB (50 to 61% sequence identity), which suggests that the plant GyrA and GyrB genes have an endosymbiotic origin (Osteryoung and Nunnari, 2003).…”
Section: N Benthamiana Homologs Of the Dna Gyrase A And B Subunitsmentioning
confidence: 97%
“…NbGyrA, NbGyrB, and other plant DNA gyrase subunits contain an N-terminal extension that features chloroplast and mitochondria targeting signals (Emanuelsson and von Heijne, 2001). Of the prokaryotic GyrA and GyrB sequences, those of cyanobacterial species are most closely related to NbGyrA and NbGyrB (50 to 61% sequence identity), which suggests that the plant GyrA and GyrB genes have an endosymbiotic origin (Osteryoung and Nunnari, 2003).…”
Section: N Benthamiana Homologs Of the Dna Gyrase A And B Subunitsmentioning
confidence: 97%
“…In the following section we will review the fission/fusion machinery focusing on the proteins that have been shown to be involved in mammalian cell death (Table 1). For a more detailed discussion of mitochondrial fission/fusion machinery see review [34][35][36][37][38][39][40].…”
Section: Overview Of Mitochondrial Membrane Dynamics Machinementioning
confidence: 99%
“…These processes require nuclear-encoded assembly factors (Grivell et al, 1999;Vothknecht and Westhoff, 2001). (v) Organelle development, for instance organelle division, which is tightly controlled by nuclear-encoded proteins (Osteryoung and Nunnari, 2003).…”
Section: Anterograde Mechanismsmentioning
confidence: 99%